Effect of Screw Configuration on the Rate of Correction for Guided Growth Using the Tension-band Plate - Kim, Nak Tscheol; Kwon, Soon Sun; Choi, Kug Jin; Park, Moon Seok; Chung, Ju Young; Han, Hee Soo; Sung, Ki Hyuk (Journal of Pediatric Orthopaedics, 2021)
Background: This study investigated the effect of screw configuration on the rate of correction of coronal angular deformity of the knee joint in children who underwent guided growth using the tension-band plate. Methods: Consecutive patients (76 patients with 154 physes; mean age: 11.8±2.2 y) who underwent guided growth using the tension-band plate for coronal angular deformity (genu varum or genu valgum) were included. The mechanical lateral distal femoral angle, mechanical medial proximal tibial angle, and screw angle were measured from the teleroentgenograms of preoperative and postoperative periodic follow-up visits. Results: The mean initial screw angle and the mean rate of correction were 16.7±10.5 degrees and 6.5±5.3 degrees per year, respectively. The rate of correction was significantly affected by age at surgery, sex, physis treated, severity of deformity, and rate of change in screw angle (all P<0.001). However, the initial screw angle and type of deformity did not affect the rate of correction. The rate of correction per year was 3.6 degrees higher in boys than in girls and 2.8 degrees higher in the distal femur than in the proximal tibia. A 1 degree increase in the rate of change in screw angle was associated with a 0.5 degree increase in the correction rate. Screw angle significantly increased with follow-up duration (P<0.001) and the change in screw angle was significantly affected by age, sex, and physis treated (all P<0.001). Conclusions: This study demonstrated that screw configuration did not affect the correction rate of coronal angular deformity for guided growth using the tension-band plate. Therefore, surgeons only need to insert the screws according to anatomic restriction, not considering the screw configuration when using the tension-band plate for guided growth in children. Level of Evidence: Prognostic level III.
Keywords: Adolescent; Bone Plates; Bone Screws; Child; Female; Genu Valgum; Humans; Male; Retrospective Studies; Tibia; coronal angular deformity; guided growth; screw configuration; tension-band plate